Question
Asked Dec 11, 2019
1 views

Solve. (If there is no solution, enter NO SOLUTION.)

y  =  x2 + 4x + 4
x + 2y  =  −1
(x, y)  = 
 
 
 
 
 (smaller x-value)
(x, y)  = 
 
 
 
 
 (larger x-value)
check_circle

Expert Answer

Step 1

Step 2

...
help_outline

Image Transcriptionclose

x+2(x + 4x + 4)=-1 x+2x? + 8x +8 =-1 2x +9x +9 =0 3 x=-3,- when x = -3, y = 3 when x = -y=1

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra